The management of the shoulder skin microbiome (Cutibacterium acnes) in the context of shoulder surgery: a review of the current literature. (October 2021) - Moore, Nathan FE; Batten, Timothy J; Hutton, Christopher EJ; White, William James; Smith, Christopher D
Background: This review aims to establish current knowledge of the shoulder skin microbiome and how to manage the bacteria that reside within it. Methods: A review was undertaken of the current literature through OvidSP. All abstracts were reviewed by three independent researchers. Results: Thirty-five studies met the inclusion criteria. With forward referencing an additional 14 were included. None commented on organisms specific to the shoulder microbiome other than Cutibacterium acnes. Therefore, this review is focussed on the current knowledge of C. acnes. Discussion: C. acnes is a skin commensal within the pilo-sebaceous glands reported to be the primary pathogen in up to 86% of shoulder joint infections. Pre-operative culture of unprepared skin can be indicative of underlying joint infection in shoulder arthroplasty revision. Intra-articular biopsies may have a high false positive due to skin contamination. Correlating the number of positive samples and certain associated signs can give a greater than 90% probability of a true infection. Standard surgical skin preparation, peri-surgical intravenous antibiotics and oral pre-operative antibiotics do not reduce bacterial load within the skin. However, topical benzoyl peroxide and clindamycin have both demonstrated significantly reduced bacteria load. Phylogenetically there are six main types. Patients may have more than one phenotype present during infection.